Recepcja żydowskich rytuałów w staropolskim apokryfie Żywot Pana Jezu Krysta - Jędrzejczak, Andrzej (Poznańskie Studia Teologiczne, 2022)
In the presented article I deal with the reception of ancient Jewish rituals by the author of the Old Polish apocryphon Żywot Pana Jezu Krysta. These are two celebrations closely related to the birth of a male descendant: the offering of the newborn and the cleansing of the mother from cultic impurity. The aim of the article is to indicate the manner in which this reception took place, as well as its theological consequences for medieval Mariology.